(untitled) (Bangladesh Journal of Microbiology, 2024)
Malate Dehydrogenase (MDH) stands as a pivotal enzyme crucial for cellular energy metabolism, orchestrating the conversion of malate to oxaloacetate in both prokaryotic and eukaryotic organisms. This study delves into the evolutionary trajectories of MDH1 (cytoplasmic) and MDH2 (mitochondrial), offering substantial evidence supporting the archaebacterial origin of eukaryotes. The dataset spans nine groups, encompassing human MDH1 and MDH2, mammalian MDH1 and MDH2, amphibian MDH2, arthropod MDH2, amoeba MDH1, archaea, and bacteria. Protein BLAST analysis revealed significant sequence homology in mammalian MDH1, particularly among primates, underlining a close evolutionary connection. Conversely, lower eukaryotes, including amoeba, arthropods, and amphibians, exhibited marked divergence from human MDH1 and MDH2. Phylogenetic analysis unveils distinct clusters for MDH1 and MDH2, accentuating significant genetic diversity between mitochondrial and cytoplasmic MDH enzymes. Prokaryotic MDH sequences cluster with human mitochondrial MDH2, while MDH1 forms a separate cluster. Staphylococcus MDH aligns with archaeal MDH, emphasizing the diversity within bacterial MDH evolution. Protein variability analysis indicates noteworthy divergence of human MDH1 from prokaryotic MDH, while MDH2 displays comparatively lower divergence. Pairwise evolutionary divergence analysis sheds light on complex relationships among MDH protein sequences. Human MDH1 shows close evolutionary ties to mammalian MDH1, whereas MDH2 exhibits a unique pattern, aligning closely with mammalian MDH2, arthropods, and amphibians. Furthermore, MDH2 demonstrates closer proximity to bacterial MDH, supporting a bacterial origin of mitochondrial MDH. In contrast, MDH1 displays less divergence to archaeal MDH than its bacterial counterpart, endorsing an archaeal origin for cytoplasmic MDH. In conclusion, this study provides compelling support for the archaebacterial origin of eukaryotes, suggesting a bacterial endosymbiont within an archaeal host that evolved into mitochondria. It contributes valuable insights into MDH evolution, unraveling the intricate relationships and unique adaptations shaping the evolutionary history of eukaryotic cells. Bangladesh J Microbiol, Volume 40, Number 1, June 2023, pp 15-24